2000
DOI: 10.1007/s002560050010
|View full text |Cite
|
Sign up to set email alerts
|

Atypical adult non-calcified pilomatricoma

Abstract: We present a rare case of a non-calcified pilomatricoma in a 67-year-old man. This tumor was extremely large in size, and its location, in the lower extremity, was very unusual. The clinical, radiographic, and histopathological features are described in detail. The role of magnetic resonance imaging (MRI) in the diagnosis of this entity is discussed. Definite internal reticulations and septations were observed.A possible explanation for this observation is that the high signal intensity reticulations may repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…PMX may be diagnosed from sebaceous cysts by noninvasive physical imaging examinations such as general radiography, ultrasound sonography, magnetic resonance imaging and computed tomography (CT) scan (Fujioka et al, 2003;Imperiale et al, 2001;Masih et al, 2000;Som et al, 1998). The majority of these techniques are capable of providing morphological or structural information, but none of them are able to provide information about the chemical composition of PMX.…”
mentioning
confidence: 99%
“…PMX may be diagnosed from sebaceous cysts by noninvasive physical imaging examinations such as general radiography, ultrasound sonography, magnetic resonance imaging and computed tomography (CT) scan (Fujioka et al, 2003;Imperiale et al, 2001;Masih et al, 2000;Som et al, 1998). The majority of these techniques are capable of providing morphological or structural information, but none of them are able to provide information about the chemical composition of PMX.…”
mentioning
confidence: 99%
“…The authors suggested that the hyperintense bands noted on the T2-weighted images might correspond to the basaloid bands present on the histologic specimens. On the other hand, Masih et al (8) put forward another possible explanation for this observation, suggesting that the high signal intensity reticulations might represent edematous stroma surrounding basaloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral enhancement of connective tissue and/or patchy or reticular central enhancement of intercellular stroma on contrast-enhanced T1W images are characteristic. 33 …”
Section: Pilomatricomamentioning
confidence: 99%